If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 5) + -4(x + 5) = 0 Reorder the terms: x(5 + x) + -4(x + 5) = 0 (5 * x + x * x) + -4(x + 5) = 0 (5x + x2) + -4(x + 5) = 0 Reorder the terms: 5x + x2 + -4(5 + x) = 0 5x + x2 + (5 * -4 + x * -4) = 0 5x + x2 + (-20 + -4x) = 0 Reorder the terms: -20 + 5x + -4x + x2 = 0 Combine like terms: 5x + -4x = 1x -20 + 1x + x2 = 0 Solving -20 + 1x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-5, 4}
| 25x^2+18=12x | | 8n-14=194 | | 4b-6a= | | -4+5=n | | 6x+2y=2 | | 3x-(-6)=24 | | x^2-35-2x=0 | | (5b-3)(5b+3)= | | (5b-3)x(5b+3)= | | 76=2(6+2w) | | 76=2w+2(6+2w) | | (5b-3)*(5b+3)= | | (5b-3)= | | 4a-3=7 | | (9+n)6=7(n-4) | | 4x^3-64x^2+240x=0 | | x^2-96=0 | | x^2-96=0 | | 7x-y=-25 | | 4y+4(-2)=12 | | 4y+4(-9)=12 | | y=2(1)-3 | | y=2(0)-3 | | y=2(-1)-3 | | y=4(2)+5 | | 4x-5=x-20 | | y=4(-1)+5 | | y=4(-6)+5 | | y+2(5)=-9 | | y+2(2)=-9 | | kx^2-10x+25=0 | | -4y+2y=2y-6+y |